2021
DOI: 10.3390/molecules26237385
|View full text |Cite
|
Sign up to set email alerts
|

Computational Simulation of HIV Protease Inhibitors to the Main Protease (Mpro) of SARS-CoV-2: Implications for COVID-19 Drugs Design

Abstract: SARS-CoV-2 is highly homologous to SARS-CoV. To date, the main protease (Mpro) of SARS-CoV-2 is regarded as an important drug target for the treatment of Coronavirus Disease 2019 (COVID-19). Some experiments confirmed that several HIV protease inhibitors present the inhibitory effects on the replication of SARS-CoV-2 by inhibiting Mpro. However, the mechanism of action has still not been studied very clearly. In this work, the interaction mechanism of four HIV protease inhibitors Darunavir (DRV), Lopinavir (LP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…Shaw Research 31 . In agreement with data from other simulations 37 , the D.E. Shaw trajectory shows low root mean square fluctuations (RMSF) outside of the C-terminal tail (Figure 2C).…”
Section: Resultssupporting
confidence: 91%
“…Shaw Research 31 . In agreement with data from other simulations 37 , the D.E. Shaw trajectory shows low root mean square fluctuations (RMSF) outside of the C-terminal tail (Figure 2C).…”
Section: Resultssupporting
confidence: 91%
“…Other examples of the application of computational tools in the development of M Pro inhibitors are: (i) the already mentioned work of Oerlemans et al who carried out molecular docking and resolved a co-crystal structure with boceprevir [ 53 ]; (ii) the thorough combination of computational tools used by Ngo et al over a database of ~4600 compounds comprising virtual screening, fast pulling of ligand (FPL), and free energy perturbation (FEP), identifying darunavir as potential SARS-CoV-2 M Pro inhibitor [ 105 ]; (iii) the approach followed by Semenov and Krivdin combining modelling of NMR chemical shifts and docking studies that found the natural compound berchemol to be a potential inhibitor [ 106 ]; (iv) the study of Yu et al applying docking, molecular dynamics (MD) simulations and MM-GBSA methods with four HIV protease inhibitors and ribavirin which provided information on blocking M Pro [ 107 ]; (v) Souza-Gomes et al also used a combined approach using machine learning, docking, MM-PBSA calculations, and metadynamics with FDA approved compounds, and they found mirabegron to form the strongest interaction with M Pro [ 108 ]; (vi) the study of Patel et al who applied docking, MD simulations, the free energy of binding, and DFT calculations on a set of 7809 natural compounds and identified theaflavin and ginkgetin as M Pro inhibitors [ 109 ]; (vii) the fluorinated tetraquinolines proposed by El Khoury et al in a computationally driven study using high resolution MD free energy binding calculations and machine learning predictions [ 110 ]; or (viii) the 28 drugs proposed by Piplani et al for repurposing as M Pro inhibitors which resulted from docking studies followed by high-throughput MD simulations of large set of natural products and licensed drugs [ 111 ].…”
Section: Computational Studies and Modellingmentioning
confidence: 99%
“…[22][23][24] Therefore, M pro is an attractive broad-spectrum antiviral target against COVID-19 as well as other pan-coronavirus. 25,26 Currently, different strategies have been developed and established to detect M pro and select its inhibitors, such as molecular docking technology, commercial kits based on fluorescence resonance energy transfer techniques, nuclear magnetic resonance spectroscopy, mass spectrometry, surface plasmon resonance, cell-based FlipGFP assay, fluorescent probes and biosensors on account of the bioluminescence resonance energy transfer. 9,19,[23][24][25][26][27][28][29] It should be noted that the molecular docking technology is only used to screen M pro inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 Currently, different strategies have been developed and established to detect M pro and select its inhibitors, such as molecular docking technology, commercial kits based on fluorescence resonance energy transfer techniques, nuclear magnetic resonance spectroscopy, mass spectrometry, surface plasmon resonance, cell-based FlipGFP assay, fluorescent probes and biosensors on account of the bioluminescence resonance energy transfer. 9,19,[23][24][25][26][27][28][29] It should be noted that the molecular docking technology is only used to screen M pro inhibitors. Although these methods could have fulfilled the need to a certain extent, still there are shortcomings to be overcome, such as background interference, instrument dependency, and time-consuming and cumbersome operation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation